Targeted drug delivery by bone cements - Kheradmand, Zahra; Rabiei, Maryam; Noori Tahneh, Akram; Shirali, Elham; Abedi, Morteza; Dashtipour, Bahareh; Barati, Elham (Journal of Composites and Compounds, 2022)
Bone cement (BC) is one of the most crucial materials for the substitution of damaged bones. Polymer or ceramic can be used as cement materials. Systemic drug delivery to the bone is difficult since human bone has limited perfusion. BC can carry drugs directly to the bone without causing adverse effects on healthy tissues, so it is a good choice for targeted drug delivery. Growth factors in addition to anti-inflammatory, anticancer, analgesic, and antibiotic reagents are just a few of the medicinal chemicals that may be added into BC for various treatment techniques. Our goal in this review is to introduce diverse BCs, drug loading mechanisms in BCs, and ultimately their clinical applications in dental potentials, inflammation therapy, bone infection, treatment of osteoporosis, coating of implants, and cancer therapy.